Microstructure, mechanical properties, and corrosion behavior of new βtype Ti–Mo–Nb based alloys by Mn addition for implant material - Sutowo, Cahya; Supriadi, Sugeng; Pramono, Andika Widya; Suharno, Bambang (Eastern-European Journal of Enterprise Technologies, 2020)
Titanium alloys are widely used for biomaterial applications since they have special characteristics, especially better biocompatibility, superior corrosion behavior and lower modulus of elasticity compared to other conventional biomaterials. The development of existing Ti6Al4V alloys by creating new β-type Ti-Mo-Nb based alloys by modifying the addition of the Mn element as a beta phase stabilizer, so that the beta phase structure can have an effect to increase strength and reduce elastic modulus with good biocompatibility and toxicity. In the present work, Ti–Mo–Nb–(x)Mn alloys (x=0, 4, 8, and 12, mass fraction in %) were prepared using an electric vacuum arc furnace with a tungsten electrode. The samples were homogenized at 1050°C for 6 h under a controlled argon atmosphere, and the effects of adding Mn on the mechanical properties and corrosion behavior of the alloys were investigated using X-ray fluorescence spectroscopy, X-ray diffraction, optical microscopy, hardness and ultrasonic tests, and potentiodynamic polarization test. The experimental results show that adding 4 %, 8 %, and 12 %Mn to a Ti–9Mo–6Nb alloy stabilizes the formation of the β-phase titanium, implying that the alloys have similar microstructures but different grain sizes. Potentiodynamic polarization measurements show that an increase of the Mn content in the Ti–9Mo–6Nb alloy decreases the corrosion resistance. At 4 %Mn, the alloy has an elastic modulus of 93 GPa and better corrosion resistance, with a relatively low corrosion rate amounting to 0.00290 mm per year, than those of a commercial Ti–6Al–4V alloy